(untitled) (Annals of Medical Research, 2022)
Aim: To determine the aerobic capacity of generalized myasthenia gravis (MG) cases and to explore the effect of aerobic exercise on maximum aerobic capacity, fatigue level, kinesiophobia, and disease severity parameters. Materials and Methods: The seropositive-confirmed generalized MG cases who were between the ages of 18 and 80 years and between 2-4 stages, at the same time hospitalized in the physical therapy and rehabilitation clinic for three weeks were included in this study. Outcome measures of the 6-minute walk test (6MWT), the ergospirometric cardiopulmonary stress test (ETT), the multidimensional fatigue scale (MFS), the Quantitative Myasthenia Gravis Score (QMG) and, the Tampa kinesophobia scale (TKS) were evaluated at admission and discharge. Results: A negative correlation between VO2 max and kinesophobia and fatigue (p= 0.020, r= -0.750; p= 0.031, r= -0.714, respectively) was determined, while a positive correlation was recorded between VO2 max and 6-MWT (r= 0.783 p= 0.013). Conclusion: Intermittent aerobic exercise programs can be safely administered under supervision in generalized MG patients. The functional capacity of the patients increased, fatigue and fear of movement decreased. Registration: The Ethics Committee in the University of Health Sciences, Diskapi Training and Research Hospital confirmed the study (Protocol #91/05 Dated 06.07.2020).